IMPLEMENTASI TEKNIK STENCIL PRINT UNTUK MENINGKATKAN KREATIVITAS ANAK USIA DINI - Nurhusna Kamil; Raden Rachmy Diana (Universitas Negeri Padang, 2023)
Creativity is one of a person's ability to be able to dedicate the results of ideas or thoughts through concrete forms or works. In creating the work should get the right stimulus from various parties. The teacher's ability to stimulate early childhood is one of the supporting factors. In addition, the use of media and teaching materials is important in efforts to increase creativity in children. One of the activities that teachers can apply to make this happen is to use the stencil printing technique. The research method used is qualitative with a sample selection of 3 people in the 5-6 year age category and classifying children's works in art activities. The purpose of this study was to find out the results of applying stencil printing techniques to increase early childhood creativity. While the data collection technique uses preliminary information obtained from class teachers and school principals as well as the results of initial observations. From the research results it is known that this technique is able to increase the creativity of early childhood in the art of coordinating colors. The new finding in this study is that the stencil printing technique can be applied to children by simplifying the tools and materials used by the teacher according to the learning needs and characteristics of the children.